Students' Interpersonal Intelligence Formulation - Muhammad Yusron Maulana El-Yunusi; M. Yunus Abu Bakar; Mardiyah Mardiyah (Al-Hayat: Journal of Islamic Education, 2022)
The totality of academic life is the most crucial and effective means for developing interpersonal intelligence, sensitivity, and ability to deal with problems and communicate well in social life. This research was conducted at Darussalam Gontor Islamic Boarding School to explain the formulation of the development of interpersonal intelligence of students (commonly called santri in Indonesian) at Islamic boarding schools. The formulation of students' interpersonal intelligence development is presented as follows: a) the dimensions of interpersonal intelligence developed and b) developing students' interpersonal intelligence. This qualitative research collects data using in-depth interviews, observation and documentation. Data analysis techniques include data reduction, data presentation and concluding and checking the validity of the data using triangulation; credibility, transferability, dependability, and confirmability. The findings of this study reinforce behavioristic theory, namely a learning theory that emphasizes changes in behaviour as a result of the interaction between stimulus and response. Changes in behaviour are a reflex of a push and response. In the development of behavioristic theory, learning and education are also the results of reactions that arise from interactions between the environment and the individual's cognitive schemes, and ultimately social learning theory (reciprocal determinism) as part of a behavioristic theory. This is a practical theory in formulating the development of interpersonal intelligence for students.